Sistem Informasi Geografis Pemetaan Sebaran Lokasi Objek Daya Tarik Wisata Kota Tasikmalaya - hikmah, agung baitul; sutisna, herlan; simpony, bambang kelana (Universitas Bina Sarana Informatika, 2023)
Administratively, Tasikmalaya City oversees 10 sub-districts with 69 villages that have an area of 183.85 Km2 with 49 locations of ODTW (Tourism Attraction Objects). With so many ODTW in Tasikmalaya City, it should be a leading tourist attraction. However, these 49 ODTW in Tasikmalaya City are not well known by the general public. This happens because the development of tourism industry promotion has not been optimized. Therefore, an application is needed to map the distribution of ODTW locations in Tasikmalaya City as a means of promoting the tourism industry in Tasikmalaya City. This research was conducted with the aim of increasing the promotion of the potential ODTW of Tasikmalaya City to attract domestic and foreign tourists which of course can increase regional income and the economy of the people of Tasikmalaya City. The method of implementing application development uses a waterfall model which has several stages in the implementation of its research. The first research stage is communication, including: (a) identification of potential, (b) identification of problems, (c) identification of application features and functions, (d) data collection. The second research stage, planning, includes: (a) team formation and division of work tasks, (b) preparation of research schedule, (c) preparation of research costs. The third research stage is modeling, including: (a) database structure design, (b) algorithm design, (c) system design, (d) interface design. The fourth research stage is construction, including: (a) code validation, (b) code testing. The fifth research stage deployment includes: (a) application program revision, (b) application program implementation, (c) application program development, (d) feedback. The results of the research are in the form of an android-based Tasikmalaya City tourist attraction location mapping application equipped with location search features, location share features and language features (Indonesian and English).Keyword: SIG; Tour; Tasikmalaya City